EVALUATION OF EFFICACY OF EPIDURAL MAGNESIUM SULPHATE AS AN ADJUVANT TO EPIDURAL LEVOBUPIVACAINE FOR POSTOPERATIVE ANALGESIA IN PATIENTS UNDERGOING FEMUR SURGERIES: A PROSPECTIVE OBSERVATIONAL STUDY - Dr. P. Rajkumar, Dr. M. Bhaskar, Dr. A. RaniPriya, Dr. K. Murugesan (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Epidural anaesthesia is a versatile central neuraxial technique. There is growinginterest in enhancing its analgesic efficacy by using adjuvants. Magnesium sulphate hasemerged as a promising agent for improving postoperative analgesia. This study aims to